Eliciting the magnitude of auditory threshold shift considered injury in Antarctic marine mammals - Verfuss, U. K.; Darias-O’Hara, A. K.; Erbe, C.; Houser, D.; Janik, V. M.; Ketten, D.; Lucke, K.; Morell, M.; Pacini, A.; Reichmuth, C.; Booth, C. G. (Marine Policy, 2024)
The Antarctic is a pristine environment inhabited by marine mammal (cetacean and pinniped) species protected by the Protocol on Environmental Protection to the Antarctic Treaty. Harming these animals is prohibited unless specifically authorised. Noise-inducing activities (e.g., seismic surveys) may lead to injury and require a prior impact assessment. This paper provides quantitative guidance to the German regulator on the significance of impacts from anthropogenic noise-generating activities on marine mammals in Antarctic waters. To support standardised impact assessments, we used an expert elicitation process to estimate the amount of temporary threshold shift (TTS) that could be considered injury as defined by German law. Experts focused on the amount of TTS that could alter the anatomical integrity of the auditory pathway, with varying views on how changes in hearing could affect an individual. They also considered potential changes in life-history functions and vital rates arising from a reduction in the animal's hearing range in a particular frequency band and the resulting impact on its ability to forage, communicate, or sense its environment acoustically. Noise sources were vessels, seismic airguns used for research, and hydroacoustic research equipment. For vessels and seismic airguns, elicited median TTS values considered injury ranged from 13.6 dB for low-frequency cetaceans to 20.5 dB for very high-frequency cetaceans. For hydroacoustic equipment, values ranged from 17.4 dB for high-frequency cetaceans to 23.4 dB for low-frequency cetaceans. The process highlighted uncertainties in how a TTS affects individuals, driven by data gaps and varying expert views, as well as future research needs.